Contrasting Host-Parasite Population Structure: Morphology and Mitogenomics of a Parasitic Flatworm on Pelagic Deepwater Cichlid Fishes from Lake Tanganyika - Kmentová, Nikol; Hahn, Christoph; Koblmüller, Stephan; Zimmermann, Holger; Vorel, Jiří; Artois, Tom; Gelnar, Milan; Vanhove, Maarten P M (Biology, 2021)
Little phylogeographic structure is presumed for highly mobile species in pelagic zones. Lake Tanganyika is a unique ecosystem with a speciose and largely endemic fauna famous for its remarkable evolutionary history. In bathybatine cichlid fishes, the pattern of lake-wide population differentiation differs among species. We assessed the congruence between the phylogeographic structure of bathybatine cichlids and their parasitic flatworm Cichlidogyrus casuarinus to test the magnifying glass hypothesis. Additionally, we evaluated the use of a PoolSeq approach to study intraspecific variation in dactylogyrid monogeneans. The lake-wide population structure of C. casuarinus ex Hemibates stenosoma was assessed based on a portion of the cox1 gene combined with morphological characterisation. Additionally, intraspecific mitogenomic variation among 80 parasite samples from one spatially constrained metapopulation was assessed using shotgun NGS. While no clear geographic genetic structure was detected in parasites, both geographic and host-related phenotypic variation was apparent. The incongruence with the genetic north-south gradient observed in H. stenosoma may be explained by the broad host range of this flatworm including eupelagic bathybatine host species that form panmictic populations across the lake. In addition, we present the first parasite mitogenome from Lake Tanganyika and propose a methodological framework for studying the intraspecific mitogenomic variation of dactylogyrid monogeneans.
Keywords: cox1; Bathybatini; Cichlidogyrus; monogenea; PoolSeq